Regulaç\~ao financeira relacionada a riscos climáticos: Notas sobre uma construç\~ao em processo - Mauro Santos Silva (Instituto de Pesquisa Econômica Aplicada (IPEA), 2024)
– Extreme climate events and factors related to the transition to a low-carbon economy can give rise to risk events capable of generating negative impacts on development financing by affecting the balance sheet of financial institutions and the stability of the financial system. The Bank for International Settlements (BIS) prepares international recommendations, and the Central Bank develops standards and metrics for financial regulation within the scope of the Brazilian economy, including regarding the exposure of financial institutions to risks arising from climate events. This new dimension of regulation, by determining a more formalized and sophisticated treatment of climate-related risks, constitutes a relevant factor in the strategy, business models of financial institutions, project risk classification, asset pricing and, consequently, it has repercussions on development financing conditions.
Keywords: G28; N2; Q01; Q54; Q56; 330; government policy and regulation; financial markets and institutions; sustainable development; climate; environment and development